2012
DOI: 10.1097/ico.0b013e31821e429d
|View full text |Cite
|
Sign up to set email alerts
|

Mitomycin C: Biological Effects and Use in Refractive Surgery

Abstract: After more than 10 years of use, MMC has been found to be effective when used for prevention and treatment of corneal haze. Questions remain regarding optimal treatment parameters and long-term safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 171 publications
(176 reference statements)
0
53
0
1
Order By: Relevance
“…Many surgeons use MMC treatment for virtually any secondary corneal surface ablation procedure in which there is a risk for significant haze. 16 Mitomycin-C is a potent mitotic inhibitor that decreases the incidence of haze after surface ablation by inhibiting the proliferation of myofibroblast presursors. 15,16 In this case, prophylactic MMC was not used in the primary PRK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many surgeons use MMC treatment for virtually any secondary corneal surface ablation procedure in which there is a risk for significant haze. 16 Mitomycin-C is a potent mitotic inhibitor that decreases the incidence of haze after surface ablation by inhibiting the proliferation of myofibroblast presursors. 15,16 In this case, prophylactic MMC was not used in the primary PRK.…”
Section: Discussionmentioning
confidence: 99%
“…16 Mitomycin-C is a potent mitotic inhibitor that decreases the incidence of haze after surface ablation by inhibiting the proliferation of myofibroblast presursors. 15,16 In this case, prophylactic MMC was not used in the primary PRK. However, the use of MMC years earlier might not prevent late haze after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested that MMC is safe and effective, although there continue to be concerns regarding long-term safety. 4 Other approaches have been explored on animal models, 5-7 but none have reached the stage of clinical testing in humans. An alternative approach to the prevention of corneal haze after trauma could be to use inexpensive autologous substances.…”
Section: Introductionmentioning
confidence: 99%
“…The possible formation of severe corneal subepithelial haze tended to limit the surface ablation procedures and the options to correct high refractive errors (13) .…”
Section: As Adjuvant Therapy After Prkmentioning
confidence: 99%